Motivated viewing: Selective exposure to political images when reasoning is not involved. (1st March 2020) - Warren, Clarisse; Schneider, Stephen; Smith, Kevin B.; Hibbing, John R.
Abstract: Motivated reasoning is an important element of politics especially in these highly polarized times. People selectively expose themselves to information in a fashion that makes it possible to embrace arguments consistent with their existing biases and ignore arguments inconsistent with those biases. Often overlooked in the research on motivated reasoning and selective exposure to information, however, is that a substantial portion of politics is about affective responses—that which makes people feel good and that which makes people feel bad. In this paper, we introduce a novel indicator of people's tendency to prolong exposure to favored political images or to truncate exposure to disliked political images. This measure makes it possible to better understand individual differences regarding concepts such as negativity bias and asymmetric political attention even when substantive, issuebased information is not at play.